Villain Figure’s Ambivalence in the Comic Gundala: Destiny - Irish Hening; Suma Riella Rusdiarti (Jurnal Lingua Idea, 2020)
In the comics with superhero genre, the reader will see a villain figure as the opponent of superhero. In September 2019, Bumilangit in collaboration with Gramedia Pustaka published the comic Gundala: Destiny as the complementary media adaptation to the movie Gundala: This Country Needs Patriots which was also published in the same year. This comic presents the figure of Sancaka against Pengkor. Unlike the movie, the main point of narration in the comic is from the perspective of Pengkor as the villain. The comic’s narrative shows the story of Pengkor's childhood until he became a mafia who is feared and respected by many people. With his power, Pengkor has both socially or politically dominance. His power also works with his 10 adopted children as the victims of his subordination. However, Pengkor’s actions to create power over his children were carried out without coercion and repression. In this way, his adopted children obeyed and glorified Pengkor with the nickname 'Father'. By using the structural theory of Tzvetan Todorov and the hegemony of power from Antonio Gramsci, this study aims to dismantle the ambivalent power attitude of Pengkor as the villain figure in the comic Gundala: Destiny.